(untitled) (Palimpsesto, 2016)
This article examines a preliminary approach to the tango fashion in the early twentieth century in some of the most important cities of the United States. We reviewed the impact caused by the arrival of this rhythm to US and how was impact of the tango on the style of dances in the mentioned cities. Besides, we explored how it was promoted by groups related with the high social circles who tried to include these rhythms in their amusement meetings.